2016
DOI: 10.1002/2016gl068818
|View full text |Cite
|
Sign up to set email alerts
|

Cone angle control of the interaction of magnetic clouds with the Earth's bow shock

Abstract: We study the interaction of magnetic clouds (MCs) with the near‐Earth environment. Recent works suggest that the bow shock crossing may modify significantly the magnetic structure of an MC, and thus its ability to drive geomagnetic storms. This change is largely controlled by the bow shock configuration, which depends on the upstream interplanetary magnetic field (IMF) orientation. From the distribution of the magnetic field orientation in 152 Earth‐impacting MCs, we determine for the first time the typical sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…For a purely radial IMF, the magnetosheath asymmetries due to the bow shock configuration should completely disappear, as the θ Bn values are then distributed symmetrically about the Sun-Earth line (see e.g. Turc et al, 2016). Therefore, there should be a value of the cone angle at which the magnetosheath asymmetries maximise, before decreasing when further reducing the cone angle to finally reach the symmetrical configuration for a purely radial IMF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a purely radial IMF, the magnetosheath asymmetries due to the bow shock configuration should completely disappear, as the θ Bn values are then distributed symmetrically about the Sun-Earth line (see e.g. Turc et al, 2016). Therefore, there should be a value of the cone angle at which the magnetosheath asymmetries maximise, before decreasing when further reducing the cone angle to finally reach the symmetrical configuration for a purely radial IMF.…”
Section: Discussionmentioning
confidence: 99%
“…This is why we did not compare our numerical results concerning M A with observations in Section 3.4. Low Alfvén Mach numbers are encountered only occasionally at Earth, but they are of great importance for solar wind-magnetosphere coupling because they are associated with extreme solar wind disturbances such as magnetic clouds (Turc et al, 2016) and they result in atypical conditions in the magnetosheath (Lavraud et al, 2013). Other studies have suggested that the Alfvén Mach number plays a role in the asymmetry (Walsh et al, 2012;Dimmock et al, 2017) but it is difficult to make a direct and meaningful comparison between all of these studies since there are extensive differences across methodologies, models, and datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the bow shock and magnetosheath properties can be significantly modified during low Alfvén Mach number conditions, which are often associated with ICMEs and magnetic clouds. This may alter the solar wind-magnetosphere coupling during extreme space weather events (Lopez et al 2004(Lopez et al , 2011Lavraud et al 2007;Lavraud and Borovsky 2008;Farrugia et al 2013;Turc et al 2016).…”
Section: Influence Of the Magnetosheathmentioning
confidence: 99%
“…This study is based on the MC catalog introduced in Turc et al [], which lists the MCs observed near the Sun‐Earth L 1 libration point from 2000 to 2014. For each of these MCs, our list also indicates in which region (i.e., solar wind, magnetosheath or magnetosphere) the following spacecraft can be found: Cluster [ Escoubet et al , ], the Time History of Events and Macroscale Interactions during Substorms (THEMIS) [ Angelopoulos , ], the Geomagnetic Tail Lab (GEOTAIL) [ Nishida , ], Interball‐Tail [ Galeev et al , ], and Double‐Star TC1 [ Liu et al , ].…”
Section: Data Set and Methodologymentioning
confidence: 99%
“…The MCs' properties, and in particular their magnetic field direction, are expected to be significantly altered through these regions, as is the case for the regular solar wind. Furthermore, we note that MCs are characterized by a low Alfvén Mach number ( M A ), generally below 5 [ Lavraud and Borovsky , ; Turc et al , ]. These low M A conditions in the solar wind alter the volume of the magnetosheath, which becomes much larger than usual as the bow shock moves outward, but also how energy is processed at the bow shock [e.g., Treumann , ], the magnetosheath flows [ Lavraud et al , ; Farrugia et al , ], the current systems in the Earth's environment [ Lopez et al , ], and more generally, the solar wind‐magnetospheric coupling during MC events [ Lopez et al , ; Lavraud and Borovsky , ; Farrugia et al , ; Myllys et al , ].…”
Section: Introductionmentioning
confidence: 99%